PENGARUH STRES KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA POLRES TULUNGAGUNG - Trisnaningtyas, Ratna Yuly; Sholihin, Ustadus; Sutapa, Heru; Fuad, A. Zaky (Commodities, Journal of Economic and Business, 2023)
The Research aims to identify the effect of work stress, work motivation, Work Environment on the perfomance of police officers of sectoral Tulungagung district Police Station . The research population in this study were members of the police from portion of the population used respondents namely 36 police officer. The data collection techniques used is questionnaire. The research uses multiple liniear regression. F test and t test for statistical analysis. The result of this research show that work motivation, job stress, work enviroment influence the police perfomance. The results showed that there was a significant effect between work stres, work motivation and work environment on employee performance with a significant value = 0,000. Calculation of regression coefficient of work motivation indicator (X2) has the highest t test value of 5,337 on employee performance. With this the work motivation (X2) has the greatest influence compared to other indicators.